Performance of members of the Regional People's Representative Council (DPRD) Takalar Regency - Henni Zainal; Andi Tahira Ashar; Andi Idham Ashar; Andi Aslinda; Ignasius Setitit (Pinisi Business Administration Review, 2021)
Performance measurement for the members of the Takalar District Parliament in implementing budget functions is only emphasized to the ability to understand budget absorption or perform the basic tasks that have been outlined.The purpose of this research is to find out the performance of members of the Regional People's Representative Council (DPRD) Takalar Regency.This type of research in this study is qualitative with a case study approach which is one type of qualitative research.Therefore, this research approach is a case study in which researchers conduct an in-depth exploration of programs, events, processes, activities, in one or more people.Data collection techniques are to use interviews, observations, and documents.The conclusion in this study is that the performance of members of the Takalar District Parliament has not been optimal.The productivity of their performance in the implementation of budget functions is influenced by factors of their educational background or knowledge related to the budget.